Taxonomy of the ant genera Leptothorax Mayr, 1855 and Temnothorax Mayr, 1861 (Hymenoptera: Formicidae) of China with descriptions of twenty-eight new species and a key to the known Chinese species - Qian, Yu-Han; Xu, Zheng-Hui (European Journal of Taxonomy, 2024)
The Chinese members of the genera Leptothorax Mayr, 1855 and Temnothorax Mayr, 1861 are reviewed based on the morphological characters of the worker caste, and 66 species are recognized in China to date. A new synonym is proposed: T. opaciabdomin (Chang & He, 2001) is a junior synonym of T. mongolicus (Pisarski, 1969). Twenty-eight new species of Temnothorax, T. bailu sp. nov., T. chun sp. nov., T. chunfen sp. nov., T. chushu sp. nov., T. dahan sp. nov., T. dashu sp. nov., T. daxue sp. nov., T. dong sp. nov., T. dongzhi sp. nov., T. guyu sp. nov., T. hanlu sp. nov., T. jingzhe sp. nov., T. lichun sp. nov., T. lidong sp. nov., T. liqiu sp. nov., T. lixia sp. nov., T. mangzhong sp. nov., T. qingming sp. nov., T. qiu sp. nov., T. qiufen sp. nov.,T. shuangjiang sp. nov., T. xia sp. nov., T. xiaohan sp. nov., T. xiaoman sp. nov., T. xiaoshu sp. nov., T. xiaoxue sp. nov., T. xiazhi sp. nov., T. yushui sp. nov., are described from China based on worker caste. Three species of Temnothorax, T. desioi (Menozzi, 1939), T. susamyri (Dlussky, 1965) and T. volgensis (Ruzsky, 1905) are recorded in China for the first time. The following eight species are recorded in a province or autonomous region of China for the first time: Leptothorax acervorum (Fabricius, 1793) is a new record in Qinghai, Sichuan and Yunnan; Temnothorax angulohumerus Zhou et al., 2010 is a new record in Guizhou and Tibet; T. argentipes (Wheeler, 1928) is a new record in Sichuan and Yunnan; T. mongolicus (Pisarski, 1969) is a new record in Inner Mongolia; T. reticulatus (Chang & He, 2001) is a new record in Beijing, Gansu, Inner Mongolia, Jilin, Shaanxi and Yunnan; T. spinosior (Forel, 1901) is a new record in Yunnan; T. taivanensis (Wheeler, 1929) is a new record in Guizhou, Sichuan and Yunnan; and T. zhejiangensis Zhou et al., 2010 is a new record in Henan and Guangxi. A key based on the worker caste is provided for the 66 known Chinese species.